ANALYSIS OF FIGURATIVE LANGUAGE IN TAYLOR SWIFT SELECTED SONGS IN “MIDNIGHT “ALBUM AND ITS CONTRIBUTION TO ENGLISH TEACHING AT SENIOR HIGH SCHOOL - Nanda, Dodi Widia; Khairita, Martiya Nurni; Revina, Silvi (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This study aims to analyzed of Figurative Language Used in selected Taylor Swift songs in the midnight album and its Contribution to English Teaching in Senior High School